PENGARUH MODEL PEMBELAJARAN BERDASARKAN MASALAH BERBANTUAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK KARAKTERISTIK ZAT DI KELAS VII SMP NEGERI 3 PERCUT SEI TUAN T. P 2016/2017 - Silitonga, Astrid M T; Harahap, Mukti Hamzah (JURNAL IKATAN ALUMNI FISIKA, 2017)
This study aims to determine the effect of problem based learning models for the outcomes of student learning in Characteristics of Substance subject in the first half semester of class VII SMP Negeri 3 Percut Sei Tuan year 2016/2017. This study is a quasi- experimental design by using two group pretest - posttest desain and using odd semester students of class VII SMP Negeri 3 Percut Sei Tuan Deli Derdang as population, which consists of nine parallel classes. The study take two classes as samples by using Cluster Random Sampling technique. The selected sample is class VI1-6 as experiment class dan class VII-1 as the control class with total 35 students in each class. Result data in the study is collected using essay test with total ten questions. The questions which will be used as research instrument is used after content validation process, observation sheet, and hypothesis test using t test. The results showed the average pretest score of experiment class was 33.77 with a standard deviation 5.87 and the average pretest score of control class was 32.83 with a standard deviation 5,52. Outcomes data after the treatment (post-test) in experiment class is 78.34 as average score and a standard deviation 8.69 which classified as high category; and outcomes data in control class is 64.60 as average score and a standard deviation 11.42. From the statistical test, the study obtained tcoum = 5,56 > ttabie = 1,99, a = 0.05. Ha is accepted and H0 is rejected, so it can be concluded that the hypothesis "there is no effect of problem based learning model to the learning outcomes of students in the characteristics of the substance subject in class VII SMP Negeri 3 Percut Sei Tuan" is accepted.